Effective Low-Intensity Strategies to Enhance School Success: What Every Educator Needs to Know. (December 2018) - Lane, Kathleen Lynne; Menzies, Holly M.; Ennis, Robin Parks; Oakes, Wendy Peia
We developed this special issue, Effective Low-Intensity Strategies to Enhance School Success: What Every Educator Needs to Know, for Beyond Behavior as a resource for educators and parents. Each article provides easy-to-access resources for readers to learn about effective, efficient, low-intensity strategies to support student engagement and limit challenging behavior. In this introductory article, we provide a rationale for focusing on these low-intensity strategies and an overview of the features of each article to follow.